Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1155/2012/174529
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pyloriin First Nations and Recent Immigrant Populations in Canada

Abstract: The diminishing prevalence of Helicobacter pylori infection among most segments of the Canadian population has led to changes in the etiologies and patterns of associated upper gastrointestinal diseases, including fewer peptic ulcers and their complications. Canadian Aboriginals and recent immigrants are among populations in which the prevalence of H pylori infection remains high and, therefore, the health risks imposed by H pylori remain a significant concern. Population-based strategies for H pylori eradicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 71 publications
(64 reference statements)
3
33
1
Order By: Relevance
“…These results paralleled US studies (Jones et al. ). As spontaneous elimination is uncommon, it is not surprising that infection in immigrants reflects that of their native country, but together, these results argue that transmission dynamics are specific to the region in question.…”
Section: Factors Known To Contribute To Disease Developmentsupporting
confidence: 88%
See 2 more Smart Citations
“…These results paralleled US studies (Jones et al. ). As spontaneous elimination is uncommon, it is not surprising that infection in immigrants reflects that of their native country, but together, these results argue that transmission dynamics are specific to the region in question.…”
Section: Factors Known To Contribute To Disease Developmentsupporting
confidence: 88%
“…A Canadian review of H. pylori prevalence found that first generation individuals who immigrated as adults (>20 years of age) had a rate of infection, and a rate of gastric cancer consistent with their country of origin, with an odds ratio of 9.7 times that of second generation individuals. These results paralleled US studies (Jones et al 2012). As spontaneous elimination is uncommon, it is not surprising that infection in immigrants reflects that of their native country, but together, these results argue that transmission dynamics are specific to the region in question.…”
Section: Length Of Infectionsupporting
confidence: 72%
See 1 more Smart Citation
“…Individuals from high-risk countries remain at risk throughout their lifetime, even if they immigrate to low-risk developed countries. H. pylori plays an important causal role in most gastric cancers, and its prevalence is also higher in immigrant populations and in economically deprived minority populations 3 4. While international guidelines support a test-and-treat strategy for H. pylori in high-risk individuals, such as those with family history of gastric cancer or chronic atrophic gastritis,5 primary care physicians in low-risk countries may be unaware of this.…”
Section: Resultsmentioning
confidence: 99%
“…H. pylori is one of the most common pathogens affecting half of the world’s population, particularly in developing countries. In Canada, there are three identified groups, including Aboriginal people, which are associated with higher risk of infection by H. pylori [24]. The pathogen causes illnesses and conditions such as chronic gastritis and peptic ulcers, and increases the risk of gastric cancer [23-25].…”
Section: Introductionmentioning
confidence: 99%